Introduction history, climatic suitability, native range size, species traits and their interactions explain establishment of Chinese woody species in Europe. Issue 11 (17th August 2016) - Feng, Yanhao; Maurel, Noëlie; Wang, Zhiheng; Ning, Lei; Yu, Fei‐Hai; van Kleunen, Mark
Abstract: Aim: A major challenge in ecology is to understand how multiple causal factors, which may interact, drive success of non‐native plants in new ranges. In this study we addressed the role of introduction history, climatic suitability, native range size, species traits and their interactions in the establishment of Chinese woody species in Europe. Location: China (native range), Europe (new range). Methods: We tested whether establishment of 449 Chinese woody species in Europe was associated with residence time (time since earliest planting), planting frequency, climatic suitability, native range size and species traits. We also considered possible nonlinear effects and interactions among these variables. For the 38 species that have established in Europe, we further tested whether these variables and interactions explained their establishment in multiple European countries. Results: Establishment of the 449 species in Europe was positively associated with residence time, planting frequency and climatic suitability. Except residence time, these factors were also positively associated with establishment of the 38 species in multiple countries. None of the traits tested had statistically significant main effects on establishment in Europe, but, for the established species, longer flowering period and having compound leaves were positively associated with establishment in multiple countries. The positive association between establishment in Europe and residence time was stronger for evergreen than for deciduous species. In addition, evergreens, unlike deciduous species, showed a positive association between establishment in Europe and fruiting duration. Moreover, establishment in multiple countries was positively associated with planting frequency for species with compound leaves but not for species with simple leaves, and the association between the establishment and fruiting duration changed from negative to moderately positive as climatic suitability increased. Main conclusions: Introduction history and climatic suitability explain most of the variation in establishment, and modulate the role of species traits, such as leaf retention, leaf type and fruiting duration.